Quality optimization of frozen redfish products - Jonsson, Asbjorn; Dargentolle, Cecile; Dang, Huong Thi Thu; Karlsdottir, Magnea; Gudjonsdottir, Maria; Arason, Sigurjon (Zenodo, 2020)
The aim of the study was twofold. Firstly, to explore the influence of time and temperature during frozen storage on lipid deterioration of red fish. That was done by comparing the effect of temperature fluctuation and abuse during frozen storage, as can be expected during transportation, on the physicochemical characteristics and lipid stability of redfish fillets. Secondly, to investigate the effect of 4 days postcatch and 9 days postcatch, and seasonal variation on the quality and storage stability of frozen red fish. Storage temperature and storage time affected the physical- and chemical properties in redfish, e.g free fatty acids, TBARS and TVB-N. Season of capture affected both the nutritional value and stability of golden redfish. The light muscle of fish caught in November was richer in EPA and DHA than in the fish caught in June. The fish caught in November was also more unstable through frozen storage, due to a more unsaturated nature of the fatty acids present, indicating that special care needs to be applied during handling and treatment of golden redfish caught at this time. The light muscle had a higher nutritional value than the dark muscle and is a good nutritional source for human consumption. However, the dark muscle was prone to lipid oxidation which may have a negative influence on the more valuable light muscle. So there seems to be need to separate them. : Funding: AVS R&D Fund (R 029-15)